Understanding the Role of Propulsion in the Prediction of Front-Crawl Swimming Velocity and in the Relationship Between Stroke Frequency and Stroke Length - Morais, Jorge E.; Barbosa, Tiago M.; Nevill, Alan M.; Cobley, Stephen; Marinho, Daniel A. (Frontiers in Physiology, 2022)
Introduction: This study aimed to: (1) determine swimming velocity based on a set of anthropometric, kinematic, and kinetic variables, and; (2) understand the stroke frequency (SF) – stroke length (SL) combinations associated with swimming velocity and propulsion in young sprint swimmers. Methods: 38 swimmers (22 males: 15.92 ± 0.75 years; 16 females: 14.99 ± 1.06 years) participated and underwent anthropometric, kinematic, and kinetic variables assessment. Exploratory associations between SL and SF on swimming velocity were explored using two two-way ANOVA (independent for males and females). Swimming velocity was determined using multilevel modeling. Results: The prediction of swimming velocity revealed a significant sex effect. Height, underwater stroke time, and mean propulsion of the dominant limb were predictors of swimming velocity. For both sexes, swimming velocity suggested that SL presented a significant variation (males: F = 8.20, p < 0.001, η2 = 0.40; females: F = 18.23, p < 0.001, η2 = 0.39), as well as SF (males: F = 38.20, p < 0.001, η2 = 0.47; females: F = 83.04, p < 0.001, η2 = 0.51). The interaction between SL and SF was significant for females (F = 8.00, p = 0.001, η2 = 0.05), but not for males (F = 1.60, p = 0.172, η2 = 0.04). The optimal SF–SL combination suggested a SF of 0.80 Hz and a SL of 2.20 m (swimming velocity: 1.75 m·s-1), and a SF of 0.80 Hz and a SL of 1.90 m (swimming velocity: 1.56 m·s-1) for males and females, respectively. The propulsion in both sexes showed the same trend in SL, but not in SF (i.e., non-significant variation). Also, a non-significant interaction between SL and SF was observed (males: F = 0.77, p = 0.601, η2 = 0.05; females: F = 1.48, p = 0.242, η2 = 0.05). Conclusion: Swimming velocity was predicted by an interaction of anthropometrics, kinematics, and kinetics. Faster velocities in young sprinters of both sexes were achieved by an optimal combination of SF–SL. The same trend was shown by the propulsion data. The highest propulsion was not necessarily associated with higher velocity achievement.